HUBUNGAN DUKUNGAN SUAMI DAN SIKAP IBU UNTUK MENYUSUI EKSKLUSIF SELAMA 6 BULAN - Fariza Indana Zulfa; Emi Sutrisminah; Meilia Rahmawati K. (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Breastfeeding is the responsibility of a woman who has a baby. The decision of the Indonesian Ministry of Health assign exclusive breastfeeding was given for 6 months and continues until 2 years old. Until now in Indonesia there are still many women who have not given exclusive breastfeeding to their babies. The failure to give exclusive breastfeeding is caused by several factors, one of which is the husband's support and mother's attitude. Objective: To determine the relationship between husband's support and the mother's attitude to breastfeed exclusively for 6 months in the Kudu Village, Semarang City. Methods: This was a descriptive qualitative study with an analytical study design with Cross Sectional. The study populations was 116 pregnant womens, the research sample was 32 third trimester pregnant womens. The sampling technique in this study uses total sampling. Results: Fisher's Exact Test analysis results on the two variables of this study obtained p value = 0.018 where p value <0.05 then Ha is accepted, which means there is a relationship between the husband's support variable and the mother's attitude to breastfeed exclusively for 6 months. Conclusion: The mayority of respondents recived husband’s support and had a good attitude for exclusive breastfeeding for 6 months.